Knowledge, Perception, and Participation of Proboscis Monkey Habitat Buffer Village Communities, Curiak Island Area - Rezeki, Amalia; Hatta, Gusti Muhammad; Arifin, Yudi Firmanul; Yunita, Rizmi (Interdisciplinary Social Studies, 2023)
Background: Indonesia has the third largest biodiversity of primate fauna in the world with 61 species, and there are 38 endemic primate species from these 61 species. One of the endangered endemic primates is Proboscis Monkey which is the mascot of the fauna of South Kalimantan. Proboscis proboscis conservation efforts are the responsibility of all parties, including the community. Community concern and participation are indicators of the success of proboscis monkey conservation. Aim: This study aims to analyze  the condition of the socio-cultural aspects of the local community around the proboscis monkey habitat in the Curiak Island area  through knowledge, perception and community participation. Method: Descriptive method with purposive sampling was used. Meanwhile, the research instruments were in the form of questionnaires distributed to the public and direct interviews. Findings: The results of this study show that  public knowledge of the existence of proboscis monkeys and their habitat on average exceeds 50%; people's perception of the existence of proboscis monkeys and their habitat on average exceeds 50%; and community participation in efforts to protect proboscis monkeys and their habitats by more than 80%.